CT and Ultrasound in the Study of Ulcerated Carotid Plaque Compared with Surgical Results: Potentialities and Advantages of Multidetector Row CT Angiography - Saba, L. (AJNR Am J Neuroradiol, 2007)
BACKGROUND AND PURPOSE: Ulceration is a severe complication of carotid plaque. The purpose of this study was to evaluate the role and the diagnostic efficacy of multidetector row CT angiography (MDCTA) and ultrasound (US) echo color Doppler (US-ECD) in the study of patients with carotid plaque complicated by ulceration through the comparison with the surgical observation. MATERIALS AND METHODS: From January 2004 to October 2005, 237 patients, for a total of 474 carotid arteries, studied at first with color Doppler US, were analyzed using CT angiography. A total of 103 patients underwent a carotid endarterectomy. We analyzed stenosis degree, plaque composition, and presence of ulcerations. In a second phase, the data were compared with the surgical results when the MDCTA indicated surgical intervention. RESULTS: MDCTA found 31 ulcerations; the surgical confirmation underlined a 93.75% sensitivity and a 98.59% specificity. US-ECD performances were 37.5% and 91.5% for sensitivity and specificity, respectively. The number of patients who showed plaque ulcerations increased with the severity of stenosis. Furthermore, ulcerations of the carotid plaque occurred more often proximal than distal to the point of maximum stenosis, and this trend increased with the severity of the stenosis. We also determined that fatty plaques were more likely to be affected by ulcerations. CONCLUSIONS: The results of our study suggest that MDCTA detects with higher sensitivity and specificity the presence of ulcerated plaque compared with US-ECD, which has been demonstrated to be less effective in this evaluation. Considering the high MDCTA sensitivity and specificity for detection of plaque ulceration, we therefore recommend MDCTA as a useful step for correct presurgical planning.